PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI PADA PEDAGANG PASAR LAMA TANGERANG - Rudy Arijanto; Jonathan; Rendy Hartono Jesse N.W; Delvien Wiefrand; Jonathan Rio Imanuel Agasi (Tech-E, 2025)
Technological progress is reshaping traditional markets, bringing improvements in speed, convenience, and reach to day-to-day trading. Digital payment platforms such as QRIS and All Payment along with e-commerce channels allow merchants to process transactions more quickly and give customers flexible, cash-free options. Although these innovations promise greater operational efficiency, widespread uptake remains uneven. Two persistent hurdles are low digital literacy and anxieties over data security, issues that often breed resistance and mistrust among stallholders. Findings from surveys and in-depth interviews suggest that tailor-made education and hands-on training are pivotal in changing perceptions. By demonstrating practical advantages like simplified bookkeeping, real-time sales tracking, and broader customer access training sessions help traders see technology as an ally rather than a threat. Equally important is the coordinated support of local governments, market management bodies, and technology vendors. Their collaboration can produce policies that lower adoption costs, provide subsidies for devices, and establish on-site help desks to address technical problems swiftly. Such institutional backing both incentivizes merchants and accelerates the diffusion of digital tools throughout the market ecosystem. Furthermore, guaranteeing reliable internet connectivity and user-friendly interfaces reduces friction in daily use, reinforcing trader confidence. Early adopters already report smoother workflows, faster customer turnover, and better record-keeping accuracy. These outcomes highlight the need for a multifaceted strategy combining capacity-building, stakeholder engagement, and infrastructure enhancement to modernize traditional commerce while safeguarding its cultural vibrancy and social relevance.